Залучення фольклорних джерел для вивчення наймитства в українській традиційній народній культурі в дослідженнях другої половини ХІХ – початку ХХІ століття - Маліков, В. (Народна творчість та етнографія, 2009)
In the article the author’s purpose is to sum up the experience of usage of folk sources in researches, in which customary relations of employment in Ukrainian traditional national culture are considered.